On-site microfluidic paper- based titration device for rapid semi-quantitative vitamin C content in beverages - Kaewchuay, Netnapit; Jantra, Jongjit; Khettalat, Chanyaphon; Ketnok, Supansa; Peungpra, Naruemon; Teepoo, Siriwan (My University, 2021)
A rapid, simple and on-site redox titration of vitamin C was accomplished using a novel microfluidic paper-based analytical device. The analysis was based on the combination of traditional redox titration and a microfluidic paper-based titration. The device was designed to have one sample zone connected to a titrant zone where ten different concentrations of iodine (titrant) were filled in each well. The top part of the device was a detection zone where the starch solution (indicator) was added. Vitamin C was added into a sample zone and then flowed to the titrant zone where the vitamin C was oxidized by the iodine. The excess iodine reacted with the starch indicator and endpoint of titration was reached when the blue-black product was observed by the naked eye in the detection zone. The proposed method for vitamin C detection showed the working range between 2.5 and 1,000 mg/L. The limit of detection was 2.5 mg/L. Time for an assay was only 3 sec. The developed paper-based device was applied to detect vitamin C in the real sample of beverage and the results corresponded to those obtained from traditional redox titration. The developed assay proved to be less reagent consumption compared to the traditional one. It is a truly portable device with no glassware and skilled personnel to require.
Keywords: Beverage; Microfluidic paper-based titration device; On-site detection; Vitamin C